Analysis of the Implementation of Radiation Occupational Safety and Health Management Systems in Radiology Installations: An Empirical Study at Regional General Hospitals in Banyumas Regency - Asri Indah Aryani; Oktia Woro; Agus Hermanto; Titi Prihatin; RSE Pujiastuti (International Conference on Science, Education, and Technology, 2023)
Objective from study This is analyze application system management safety and health Work radiation on installation radiology at the district hospital Banyumas . Type research used _ in study This is study method mix . Data validation is carried out with use technique triangulation , that is triangulation sources and data. Triangulation source done with method check the data obtained through a number of source . Based on results and discussion can concluded that power in work units district hospital radiology Banyumas has 2 (two) Specialists Radiology , 1 ( one ) officer Protection Radiation and 5 (five) Radiographers Diploma three . In accordance with Regulation Head of the Nuclear Energy Regulatory Agency Number 8 of 2011. There are 5 variables tested in application System Management Occupational Safety and Health Radiation On Installation Radiology . From fifth variable Licensing , management requirements , requirements security , requirements technical and testing security of the 14 processed components (50 points ) 25 points (50.34%) were fulfilled standards / regulations . A total of 11 points (22.45%) were met , however No in accordance with standard . Limitations Focus study This only on one House sick , so the analysis limited . Moment researching more further , preferably use more from one item for can compare result .